Adhesion, friction and viscoelastic properties for non-aged and aged Styrene Butadiene rubber. (May 2018) - Rodriguez, N.; Dorogin, L.; Chew, K.T.; Persson, B.N.J.
Abstract: We study adhesion and friction between smooth glass, and fresh and aged Styrene Butadiene – Isoprene rubber blend (SBR-IR). The friction and adhesion are only slightly modified by the aging process, but elongation at break, and rubber toughness, are strongly reduced. We attribute this to changes in the crosslink density, a decrease in the filler matrix strength, and to the formation and growth of crack-like defects. The latter have a small influence on adhesion and friction, but a large effect on the elongation at break. Highlights: The Influence of aging on adhesion, friction and the mechanical properties of SBR-IR rubber is studied. We show that aging can strongly reduce the elongation at break and toughness. We demonstrate that aging has a little effect on friction and adhesion. We propose growth of microcracks during aging influence the mechanical properties of the rubber.